Faire face aux inégalités de mobilité - Yves Jouffe; David Caubel; Sylvie Fol; Benjamin Motte-Baumvol (Cybergeo)
Many poor households cannot meet the requirements of automotive mobility. They suffer great inequalities in their daily mobility, especially when they live away from urban centers, in areas where the provision of public transport and local amenities are reduced. Nevertheless, a normative interpretation in terms of shortages, based on the observation of low mobility capacity, underestimates the concrete mobility practices of poor households, and secondly how these households bypass the injunction of mobility required of them. This set of alternative practices – be they tactics, strategies, and projects – can substitute expensive automotive mobility with a set of resources drawn fundamentally from spatial proximity. This article aims to analyze the diversity of these practices, their quantitative importance and nesting, for the case of Paris suburban and periurban areas. To conclude, it draws how the variety of adjustments exhibited by poor households could be taken into account by public action.